PENYULUHAN TENTANG PEMBERIAN KOMPRES HANGAT JAHE MERAH PADA PENURUNAN NYERI OSTEOARTHTRITIS - Muhammad Firdaus; Marian Tonis; Abdul Zaky; Akmal Darman Putra; Sandya Bunga Prathivi (LPPM Universitas Awal Bros, 2020)
Ginger is the most commonly used medicinal plant in the world. Its rhizome which contains zingiberol has been shown to reduce inflammation and joint pain. Osteoarthritis is a chronic joint area characterized by abnormalities in the cartilage (cartilage) of the joints and adjacent bones. Based on a preliminary survey conducted at UPT PSTW Khusnul khotimah Pekanbaru, almost 90% of the elderly had osteoarthritis. This community service is carried out in the city of Pekanbaru with the aim of providing knowledge to the public about offering red ginger warm compresses to reduce osteoarthritis pain, providing knowledge to the public regarding the effectiveness of providing red ginger warm compresses to reduce osteoarthritis pain and as input in order to provide motivation to improve management presents a warm compress of red ginger against osteoarthritis pain in the elderly. The results of this activity are expected for the community to make warm compresses of red ginger as an alternative way to reduce osteoarthritis pain.